Exploring MSME Interest in Artificial Intelligence for Financial Reporting: Surabaya-Bojonegoro Case Study - Perkasa, Riki Saputra; Widianto, Rian Tri (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to explore the interest of Micro, Small, and Medium Enterprises (MSMEs) in Surabaya and Bojonegoro towards adopting Artificial Intelligence (AI) technology for financial reporting, and to understand the influencing factors. AI holds significant potential for enhancing efficiency and accuracy in financial processes. This study utilizes a qualitative, explorative approach, with data collected through semi-structured interviews with 53 culinary MSMEs (23 in Surabaya, 30 in Bojonegoro). Analysis was conducted using the Technology, Organization, and Environment (TOE) Framework. Preliminary results indicate Surabaya MSMEs show higher AI interest for financial reporting than those in Bojonegoro. This difference stems from variations in digital infrastructure and literacy (Technology), organizational understanding and motivation (Organization), and environmental support (Environment). Despite existing interest, many lacks technical capacity. This study provides insights for local governments, universities, and business mentors to design effective digital literacy and AI training programs, fostering improved financial management and local economic transformation.